193 Growth performance of lambs and kids on pasture - Schoenian, Susan (J Anim Sci, 2020)
There are different methods for growing and finishing lambs and kids. A high percentage of lambs are finished on concentrate diets. At the same time, there is a growing demand for grass-fed meat. Grass-fed meat usually has a more healthful fatty acid profile. The gains obtained on pasture are often more economical. However, there are also challenges to raising lambs and kids on pasture. Performance (ADG and BCS) can be poor, due to seasonal fluctuations in pasture quality (and quantify), poor grazing practices, and heavy burdens of gastro-intestinal parasites (worms). Raising lambs and kids profitably on pasture requires strategies that provide excellent nutrition and minimize the impact of parasites, while meeting the desires of today’s consumers.